Prediction of tensile strength of friction stir weld joints with adaptive neuro-fuzzy inference system (ANFIS) and neural network - Dewan, Mohammad W.; Huggett, Daniel J.; Warren Liao, T.; Wahab, Muhammad A.; Okeil, Ayman M. (Materials & design, 2016)
Friction-stir-welding (FSW) is a solid-state joining process where joint properties are dependent on welding process parameters. In the current study three critical process parameters including spindle speed(N), plunge force (Fz), and welding speed (V) are considered key factors in the determination of ultimate tensile strength (UTS) of welded aluminum alloy joints. A total of 73 weld schedules were welded and tensile properties were subsequently obtained experimentally. It is observed that all three process parameters have direct influence on UTS of the welded joints. Utilizing experimental data, an optimized adaptive neuro-fuzzy inference system (ANFIS) model has been developed to predict UTS of FSW joints. A total of 1200 models were developed by varying the number of membership functions (MFs), type of MFs, and combination of four input variables (N,V,Fz,EFI) utilizing a MATLAB platform. Note EFI denotes an empirical force index derived from the three process parameters. For comparison, optimized artificial neural network (ANN) models were also developed to predict UTS from FSW process parameters. By comparing ANFIS and ANN predicted results, it was found that optimized ANFIS models provide better results than ANN. This newly developed best ANFIS model could be utilized for prediction of UTS of FSW joints. Development of a model to predict UTS from FSW process parameter. [Display omitted] •FSW joint tensile properties are dependent on welding process parameters.•A total of 73 weld schedules were welded and tensile properties obtained.•An optimized ANFIS model was developed to predict UTS from weld process parameters.•An optimized ANN model was also developed for comparison.•Optimized ANFIS model provides better results than ANN model.